INTERPRETATION OF MODIFICATION OF ARTISTIC COMPONENTS - Ismailova , Khurliman (Mental Enlightenment Scientific-Methodological Journal, 2023)
This article talks about the renewal of poetic interpretation and the synthesis of M.Sholokhov's traditions in the creation of a plot and composition, and the branching of the creative concept. Kariya", "Uzbek Character", O.Umarbekov's novel "Flower Selling Girl", the criteria of poetological construction were perceived in a unique way. As a result, radical changes in the essence of the word prepared the ground for the more attractive appearance of the modified aspects of the architecture of humanities (fiction).